No Child Left Behind: Implications for Special Education Students and Students with Limited English Proficiency - Jewell, Mark E. (Journal of the American Academy of Special Education Professionals, 2008)
This article examines the controversy that continues to surround the No Child Left Behind (NCLB) Act. Since its passage, NCLB has been criticized for a number of reasons. One of the criticisms is that it is unfair to include special education students and students with limited English proficiency in the accountability system and judge them by the same standard used for all other students. Proponents of NCLB counter that the law was designed to ensure that students in subgroups with low percentages of students meeting standards would receive attention in schools. Educators have become concerned that excluding students from testing may be harmful to students because it allows their needs to remain unknown and unaddressed. As standardized testing has taken on increasing importance in the evaluation of students, teachers, and schools, so too has the preparation of students to take these tests. Clearly, the best way to prepare students for tests is to teach them the content. In addition, students need to receive instruction in appropriate test taking strategies that will help improve test performance and reduce test anxiety.